Bark Food. The Continuity and Change of the Pine Inner Bark Use for Food by Sámi People in Northern Fennoscandia - Bogdanova, Sandra (UiT Norges arktiske universitet, 2016)
This thesis is a cultural document, a study of the Scots pine (Pinus Sylvestris L.) inner bark use, as a source of food and medicine among the Indigenous Sámi people of Northern Fennoscandia. The questions that drove this research centered on the methods and reasons people have developed over time for using Scots pine inner bark. It is still largely considered a ‘food taboo’ and is mostly associated with the years of crop failure. This research is written in indigenous studies with the elements of anthropology and ethnobotany. Using these interdisciplinary fields it becomes possible to locate the effect of such taboos and other burdens of history to the Sámi community. There are three major analytical pillars that hold up the content of this thesis. First, the literary encounters of bark food narratives, that were historically documented across Fennoscandia. Second, detailed ‘bark food’ practices and processes in the Sámi culture. Third, the availability of local resources and ethical dimensions of collecting, exhibiting,, curating and representing such Sámi traditional food related material at a local museum. The thesis argues that the Sámi have been using Scots pine inner bark as a source of food continuously and that whilst this tradition has changed it has not been lost. The key finding is a record of ‘bark food’ tradition continuity among the case study community in Northern Finland. My intention is to contribute to the politics of appreciation, of Indigenous food traditions, recognized as part of their identity and as intangible cultural heritage, including a choir of native voices, both in a historical and a contemporary perspective.